2009
DOI: 10.1200/jco.2009.23.0805
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Predictors of Progression-Free and Overall Survival in Patients With Newly Diagnosed Glioblastoma: A Prospective Translational Study of the German Glioma Network

Abstract: Purpose The prognostic value of genetic alterations characteristic of glioblastoma in patients treated according to present standards of care is unclear. Patients and Methods Three hundred one patients with glioblastoma were prospectively recruited between October 2004 and December 2006 at the clinical centers of the German Glioma Network. Two hundred fifty-eight patients had radiotherapy, 199 patients had temozolomide, 189 had both, and seven had another chemotherapy as the initial treatment. The tumors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
424
8
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 544 publications
(490 citation statements)
references
References 28 publications
41
424
8
14
Order By: Relevance
“…10,11,13,38,40,41 The 2 year and 5 year survival rates in patients with a methylated MGMT promoter treated with concomitant and adjuvant temozolomide were 49% and 14%, respectively, while the corresponding figures for patients initially treated with radiotherapy only were 24% and 5%. Of patients with an unmethylated MGMT promoter, 15% and 8% were alive at 2 years and 5 years, respectively, after treatment with combined chemoradiotherapy, compared with 2% and 0% in those initially treated with radiotherapy alone.…”
Section: The Role Of Mgmt In Glioma Subtypes Glioblastomamentioning
confidence: 99%
“…10,11,13,38,40,41 The 2 year and 5 year survival rates in patients with a methylated MGMT promoter treated with concomitant and adjuvant temozolomide were 49% and 14%, respectively, while the corresponding figures for patients initially treated with radiotherapy only were 24% and 5%. Of patients with an unmethylated MGMT promoter, 15% and 8% were alive at 2 years and 5 years, respectively, after treatment with combined chemoradiotherapy, compared with 2% and 0% in those initially treated with radiotherapy alone.…”
Section: The Role Of Mgmt In Glioma Subtypes Glioblastomamentioning
confidence: 99%
“…Putative genetic and epigenetic prognostic factors have been investigated in order to optimize treatment strategies. These include 1p/19q codeletion, isocitrate dehydrogenase (IDH) 1 and 2 gene ( IDH1/2 ) mutations, and methylation of the O(6)‐methylguanine‐DNA methyltransferase (MGMT) promoter 2, 3, which confer a better responsiveness to radio‐ and chemotherapy 4, 5, 6, even the disease is still incurable. A prominent feature of GBM is the aberrant angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this gene is strongly involved in the biology of gliomagenesis (Ducray et al., 2011; Takano et al., 2012). The IDH1 gene may be the key in the pathogenic processes associated with the R132H mutation and those caused by the accumulation of R2‐HG (Ducray et al., 2011; Mellai et al., 2011; Parsons et al., 2008; Thota et al., 2012; Weller et al., 2009). This accumulation produces a high intracellular metabolic stress, so cells need to get adapted to this condition to facilitate survival and tumor progression (Van Lith et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the survival analysis, previous studies demonstrated the prognostic significance of IDH1 mutations (Arita et al., 2015; Brennan et al., 2013; Ducray et al., 2011; Hartmann et al., 2010; Killela et al., 2014; Lewandowska et al., 2014; Mellai et al., 2011; Olar et al., 2012; Parsons et al., 2008; Polivka et al., 2014; Sanson et al., 2009; Shibahara et al., 2011; Sun et al., 2013; Takano et al., 2012; Weller et al., 2009). Some authors observed that OS and PFS in IDH mutated cases were about twice longer than in wild‐type patients (Arita et al., 2015; Polivka et al., 2014), and others showed that mutation in IDH1 was an independent factor for a favorable prognosis (Brennan et al., 2013; Ducray et al., 2011; Polivka et al., 2014; Sanson et al., 2009; Shibahara et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation